Assessment in the clinical experience: student teaching and the edTPA. Issue 4 (2nd October 2019) - Hébert, Cristyne
ABSTRACT: This article examines the edTPA, an assessment for teacher candidates in the United States that, in traditional teacher education programs, is completed within a student teaching placement. Exploring literature that highlights the function of the placement and the role of the teacher education program and cooperating teacher in shaping the placement, this text engages in an analysis of edTPA handbooks to explore how the edTPA frames the clinical experience. Findings suggest that the edTPA mischaracterizes student teaching within the clinical experience as teaching, positioning candidates as autonomous agents over their practice and the student teaching classroom, while failing to adequately acknowledge both external restrictions imposed on candidates and the educational nature of the clinical experience.